WE NEED PROTECTION: REVIEWING CORPORATE RESPONSIBILITIES AND STRATEGIES IN PROTECTING EMPLOYEES DURING THE COVID-19 PANDEMIC - Zaid Zaid; Anggraeni Pratama Indrianto; Hilwan Firhan Adityaningrat (Journal Health & Science : Gorontalo Journal Health and Science Community, 2021)
Organizations during the COVID-19 outbreak, as they are today, are faced with an external crisis that creates increased uncertainty among their employees and poses an immediate threat to their health and safety. Therefore, this study objects to further discuss the company's legal and ethical responsibilities towards employees during the COVID-19 pandemic situation. Based on the objective, this research method is included in normative research with a statutory and conceptual approach. After analyzing the data, this research then reveals, in the results of the study, that companies have legal and ethical responsibilities in saving their employees from COVID-19. Two strategic schemes are offered, including work from home and work from office by implementing strict health protocols based on applicable law. Research related to corporate responsibility to consumers during the COVID-19 outbreak is also further suggested in this study for future research.